2018
DOI: 10.1016/j.str.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Second-Shell Basic Residues Expand the Two-Metal-Ion Architecture of DNA and RNA Processing Enzymes

Abstract: SummarySynthesis and scission of phosphodiester bonds in DNA and RNA regulate vital processes within the cell. Enzymes that catalyze these reactions operate mostly via the recognized two-metal-ion mechanism. Our analysis reveals that basic amino acids and monovalent cations occupy structurally conserved positions nearby the active site of many two-metal-ion enzymes for which high-resolution (<3 Å) structures are known, including DNA and RNA polymerases, nucleases such as Cas9, and splicing ribozymes. Integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(87 citation statements)
references
References 70 publications
6
81
0
Order By: Relevance
“…Thus, in silico modelling strongly suggests that polymerases will selectively incorporate only the S p P-alkyl-phNTP diastereoisomers, which preserves the critical interaction of the negatively charged pro R p -oxygen with the catalytically essential proximal Mg 2+ ion (Mg A ) in the polymerase active site28, 30. Indeed, this is consistent with previous results that suggested stereospecific incorporation of only the S p P-Met-phTTP by Terminal transferase21.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, in silico modelling strongly suggests that polymerases will selectively incorporate only the S p P-alkyl-phNTP diastereoisomers, which preserves the critical interaction of the negatively charged pro R p -oxygen with the catalytically essential proximal Mg 2+ ion (Mg A ) in the polymerase active site28, 30. Indeed, this is consistent with previous results that suggested stereospecific incorporation of only the S p P-Met-phTTP by Terminal transferase21.…”
Section: Resultssupporting
confidence: 88%
“…Our theoretical investigations unequivocally showed that only the S p phATP substrates were able to productively engage (and remain) within the polymerase holoenzyme active site (thus forming the polymerase-primer-template complex). This is demonstrated by three different and well-established structural/chemical determinants we monitored along the 6 μ s of MD trajectory to evaluate the reactivity of the precatalytic complex; namely: i) the root-mean-square deviation (RMSD) of the incoming substrate measuring its stability within polymerase active site27, ii) the length between the -3’O - (-3’OH) nucleophile of the primer 3’-end and the α-Phosphorus of the incoming phATP assessing the formation of a prone-to-react Michaelis-Menten complex28 and iii) the ability to form Watson-Crick (WC) H-bonds to the instructive template base, a condition known to further assist the incorporation of the incoming nucleotide to the growing primer strand29, 30.…”
Section: Resultsmentioning
confidence: 99%
“…This residue is in close proximity to the branch site 39 , it interacts with the 5′-splice site, and it undergoes a rearrangement between the splicing steps 40 in a process that is modulated by protein subunits (i.e. Prp8, Prp16) 41,42 and potassium ions 43,44 . Such reorganization of G52 facilitates the release of the 5′-end of spliceosomal introns from the active site after the first splicing step, while also favoring the recruitment of the 3′-splice junction into the active site for the second step of splicing 40 .…”
Section: And Supplementarymentioning
confidence: 99%
“…Another intriguing aspect is the recurring presence of second-shell positively charged residues that surround the metal-aided catalytic site in nucleic-acid-processing enzyme. 3 During our extended MD simulations, we observed the interaction of Arg93, along the helical arch, with the terminal phosphate of the substrate. We structurally aligned hExo1 (PDB ID 5V0E) 23 with hFEN1 (PDB ID 5KSE), 34 and we noted that the terminal guanidine, amide, and amine groups of Arg93, Asn124 (in hExo1), and Lys132 (in hFEN1) residues were all within a sphere of ∼3 Å and close to the 5′ phosphate in the leaving group ( Figure S12 ).…”
Section: Discussionmentioning
confidence: 95%